Analysis of Security Aspects of User Authentication of Registration Officers in Electronic Medical Records at the Assalammedicare Clinic: Analisis Aspek Keamanan Autentikasi Pengguna Petugas Pendaftaran pada Rekam Medis Elektronik di Klinik Assalammedicare - Zahirah, Inaya; Putry, Ayu Dwiyanti; Nur Cahyani; Della, Amellia Rahma; Deqi, Alvira Permata (Jurnal Rekam Medis dan Informasi Kesehatan, 2025)
Advances in information technology have encouraged healthcare facilities, including the Assalammedicare Clinic, to implement a cloud-based Electronic Medical Records (EMDR) system. This study aims to analyze the implementation of patient data security within the EMR system at the Assalammedicare Clinic, specifically the aspects of confidentiality, integrity, and availability. The study employed qualitative methods through observation, interviews, and documentation in the registration area. The results indicate that the clinic has a data protection SOP, labeling documents "confidential," and individual access authentication for registration staff and healthcare workers. The clinic also uses the ASSIST and MEA applications to support access control. Although there have been no data breaches, challenges encountered include limited human resources with medical records backgrounds, the lack of CCTV, and slow SIMRS servers, which can impact data security and accuracy. In conclusion, the implementation of data security at the Assalammedicare Clinic is quite good, but needs to be improved through the addition of competent human resources, supporting infrastructure, and regular training. This research is expected to provide the basis for recommendations for improving patient data security in the digital era. Keywords: Electronic Medical Records, data security, user authentication